HBV Perinatal Transmission. (22nd April 2013) - Umar, Muhammad; Hamama-tul-Bushra,; Umar, Shifa; Khan, Haider Ali
Abstract : Hepatitis B is a serious public health problem all around the world. It is a blood-borne and sexually transmitted DNA virus in adults, but mother to child transmission of hepatitis B virus also occurs in infants born to hepatitis B surface antigen positive mothers.